Binding of serum ferritin to concanavalin A in patients with iron overload and with chronic liver disease. Issue 5 (May 1982) - Chapman, R W; Gorman, A; Laulicht, M; Hussain, M A; Sherlock, S; Hoffbrand, A V
Abstract : Total serum ferritin and the proportion of serum ferritin binding to concanavalin A (glycosylated ferritin) was measured in 18 healthy volunteers and in 84 patients, eight with primary haemochromatosis, 43 with beta-thalassaemia major and secondary iron overload and 33 with chronic liver diseases without iron overload. The total serum ferritin was either equally or even more closely related than either the non-binding or the concanavalin A binding ferritin, to the liver iron concentration in all patients with iron overload, and with the units of blood transfused in non-chelated thalassaemic patients. The total serum ferritin showed a significant correlation with serum aminotransferase for the group of 84 patients. In the thalassaemic patients the ferritin binding to concanavalin A also correlated with aminotransferase. However, in the other groups it was the ferritin not binding to concanavalin A which showed a significant correlation with aminotransferase activity. These results suggest that measuring the fraction of serum ferritin which binds to concanavalin A does not offer any advantage over estimation of the total serum ferritin concentration in the assessment of iron stores in patients wit iron overload and liver damage.